Conference on The Memory of the World in the Digital Age: Digitization and Preservation - Yaşar Tonta (Türk Kütüphaneciliği)
The international conference on “The Memory of the World in the Digital Age: Digitization and Preservation” was organized to commemorate the foundation of UNESCO’s Memory of the World Programme and to increase the awareness of the preservation of digital cultural heritage. It took place in Vancouver, Canada, from September 26-28, 2012, with the participation of more than 500 delegates from 110 different countries. This report summarizes some of the topics discussed during the conference.